2007
DOI: 10.1097/ta.0b013e31802bf009
|View full text |Cite
|
Sign up to set email alerts
|

The Increasing Use of Chest Computed Tomography for Trauma: Is it Being Overutilized?

Abstract: There has been a 10-fold increase in use of CCT for trauma evaluation. Although occult findings increased, the number of patients who needed treatment was small. The excess utilization of CCT after negative CXR needs continued refinement to identify the small number of potentially lethal injuries while reducing the number of trivial findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
70
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 13 publications
3
70
1
3
Order By: Relevance
“…Another negative point is that long-term use of routine immediate TBCT probably affects the quality of surgeons' skills in history taking and physical examination of trauma patients. It also may lead to findings of questionable clinical importance [4,5].…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Another negative point is that long-term use of routine immediate TBCT probably affects the quality of surgeons' skills in history taking and physical examination of trauma patients. It also may lead to findings of questionable clinical importance [4,5].…”
Section: To the Editormentioning
confidence: 99%
“…However, it should be noted that selective use of conventional cervical, chest, or pelvic imaging instead of routine radiography for all patients can be significantly time saving [4,5]. In this respect, a review of the literature turned up several articles regarding efforts made to develop some criteria for the use of selective radiography in trauma cases.…”
Section: To the Editormentioning
confidence: 99%
“…Several authors reported the detection of clinically significant findings more frequently on CCT in 'high risk' blunt trauma admissions, These patients included but were not limited to high-speed motor vehicle collisions, >15 foot falls, pedestrian versus motor vehicle collisions, patients with any sign of thoracic trauma on physical examination or any mediastinal abnormalities on CxR (Demetriades et al, 1998;Exadaktylos et al, 2001). A significant number of these patients (14-65%) can have a completely normal CxR (Trupka et al, 1997;Demetriades et al, 1998;Exadaktylos et al, 2001;Plurad et al, 2007). The lethality of the occult injury defines the urgency and pertinence of subsequent clinical action.…”
Section: Commentmentioning
confidence: 99%
“…The increased use of CCT for blunt trauma, presumably for the diagnosis BAI, has not resulted in a significant increase in detection overall. It can also be questioned as to whether all occult BAIs needs to be treated, because this probably was the case before the evolution of the CCT (Plurad et al, 2007). The question is, when should CT be used in the general blunt trauma population?…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation